Greek legacy to critical thinking - Miranda, Felipe B. (U.P. Diliman Interactive Learning Center, 2005)
The second in a series of four lectures under the project Exploring the Technology of Videoconferencing in Teaching Social Science II: a general education course on the social, economic and political thought.